Characterizing spatio-temporal coupling of extreme ultraviolet ultrashort pulses from high harmonic generation - Wyatt, A; Witting, T; Monmayrant, A; Walmsley, I; Haworth, C; Robinson, J; Tisch, J; Marangos, J (2007)
We demonstrate a tool for performing measurements of space{time coupling of ultrashort, extreme ultraviolet pulses from high harmonic generation which can be used to study propagation and phasematching effects during the generation process. © 2006 Optical Society of America.